INTELLECTUAL CAPITAL : TOWARD THE DEVELOPMENT OF CONCEPTUAL FRAMEWORK FOR ITS STANDARDIZED REPORTING - Umi Suswati Risnaeni (IQTISHODUNA: Jurnal Ekonomi Islam, 2015)
In recent year there is an increasing awareness of the significance of IC toward increasing the competitive advantage of companies. The subjective nature of IC leads to the diversity in definitions and different way of classifications as developed by researchers in the previous literatures. We are generally in agreement with Choong (2008) who classified IC systematically into four classes, which are human capital, structural capital, customer capital, and intellectual property capital.